KONSEP SYÛRÂ DALAM PANDANGAN FIQH SIYÂSAH - Moh. Zahid (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2009)
Al-Qur’ân stipulation on syûrâ, as principal law, is exceedinglyshort; the detailed ways to perform it has been absence. TheHoly Qur’ân does not persist whether the social problems mustbe determined on the basis of syûrâ, also on the matter that issyûrâ specifically applicable on government issues? Yet theProphet Muhammad saw. didn’t recommend certain outlines tobe followed. It was reflected on the method of leadersubstitution done by khalîfah after his period of time. Theprocess of substitution was merely different among one toanother. The unspecific explanation on syûrâ, takes it into aflexible, smooth and appropriate to any situation and to thewhole social problems. Consequently, the concept of al-Qur’ânon syûrâ is not identical with democracy, though its idea hashighly appreciated the major opinion as stated in democracythought.